Association of multiple metabolic and cardiovascular markers with the risk of cognitive decline and mortality in adults with Alzheimer’s disease and AD-related dementia or cognitive decline: a prospective cohort study - Liu, Longjian; Gracely, Edward J.; Zhao, Xiaopeng; Gliebus, Gediminas P.; May, Nathalie S.; Volpe, Stella L.; Shi, Jingyi; DiMaria-Ghalili, Rose Ann; Eisen, Howard J. (Frontiers in Aging Neuroscience, 2024)
There is a scarcity of data stemming from large-scale epidemiological longitudinal studies focusing on studies of potentially preventable and controllable risk factors for Alzheimer's Disease (AD) and AD-related dementia (ADRD). We aimed to test the impact of multiple metabolic factors and cardiovascular disorders on the risk of cognitive decline and AD/ADRD.: We analyzed a cohort of 6,440 participants 45 to 84 years of age at baseline. Multiple metabolic and cardiovascular disorder factors included the five components of the metabolic syndrome (waist circumference, high blood pressure [HBP], elevated glucose and triglyceride [TG] concentrations, and reduced high-density lipoprotein cholesterol [HDL-C] concentrations), C-reactive protein (CRP), fibrinogen, interleukin-6 (IL-6), factor VIII (F8), D-Dimer, and homocysteine concentrations, carotid intimal-medial thickness (CIMT), and urine albumin to creatinine ratio (ACR). Cognitive decline was defined using the Cognitive Abilities Screening Instrument (CASI) score, and AD/ADRD cases were classified using clinical diagnoses. Results: Over an average follow-up period of 13 years, HBP and elevated glucose, CRP, homocysteine, IL-6 and ACR concentrations were significantly associated with the risk of mortality in those with incident AD/ADRD or cognitive decline. Elevated D-Dimer and homocysteine concentrations, and elevated ACR were significantly associated with incident AD/ADRD. Elevated homocysteine and ACR were significantly associated with cognitive decline. A dose-response association was observed, showing that an increased number of exposures to multiple risk factors corresponded to a higher risk of mortality in those with cognitive decline or those with AD/ADRD. Conclusions: Findings from our study reaffirm the significance of preventable and controllable factors, including HBP, hyperglycemia, elevated CRP, D-Dimer, and homocysteine concentrations and ACR as potential risk factors for cognitive decline and AD/ADRD.